Hubungan Tekanan Teman Sebaya dengan Harga Diri Siswa SMP - Kinanti, Rinjani Putri; Zikra, Zikra (Lembaga Yasin AlSys, 2025)
The existence of students with poor self-esteem those who doubt their own skills, are timid when speaking in front of the class, experience fear and anxiety when confronted with challenges, and minimize their abilities was the driving force for this study. (1) To describe the self-esteem of SMP Muhammadiyah 6 Padang students; (2) to describe the peer pressure that students at SMP Muhammadiyah 6 Padang experience; and (3) to determine whether there is a relationship between peer pressure and students' self-esteem. Descriptive and correlational models are used in this kind of quantitative study. Using the stratified random selection approach, 111 students were selected from the 153 students enrolled at SMP Muhammadiyah 6 Padang during the 2024–2025 academic year, which served as the study's population. A self-esteem measure and a peer pressure scale were utilized to collect data for this study. With the aid of SPSS version 20, the data was processed using descriptive analytic methods and Pearson product moment correlation analysis. According to the study's findings, (1) students' self-esteem falls into the low category (42.34%), (2) students' experiences of peer pressure fall into the high category (45.05%), and (3) correlation analysis reveals a significant and negative relationship between peer pressure (X) and students' self-esteem (Y), with a significance level of 0.000 ˂ 0.05 at a weak relationship level, or -0.329. The findings of this negative and significant connection suggest that students' self-esteem tends to decrease with increasing peer pressure and increase with decreasing peer pressure. According to the study's findings, BK instructors and counselors may offer subject mastery services that include resources on enhancing social skills as well as individual and group therapy.